In Situ Strain Measurements Within Helmet Padding During Linear Impact Testing - Xu, Sheng; Brannen, MacKenzie; Ouellet, Simon; Brownridge, Ryan; Petel, Oren E. (Annals of biomedical engineering, 2022)
Drop and Impact testing of helmets are used extensively in the design process and eventual certification of helmets. These techniques have traditionally relied heavily on the measurement of the kinematic response to impact, which provides an indirect measurement of the liner response that is subject to interpretation during the design process. In the present work, we introduce an in situ experimental technique that provides a time-resolved measurement of the deformation of the helmet and its components during an impact event. The data collected from a high-speed X-ray imaging system can provide a full description of the deformation at the component level, which provides a helmet designer further insight into the performance of their helmet, while also returning the traditional kinematic metrics. The data presented focuses on the deformation of a commercial hockey helmet subjected to a series of linear impacts with three different impactor caps at speeds ranging from 2.4 to 4.5 m/s. Deformation of the liner was monitored in the midsagittal and a parasagittal plane of the helmet. The results show that there is a clear dependence on the maximum strain achieved in the foam that is dependent on the impact type, the impactor shape, and the resulting strain rate of deformation in the foam liner. These techniques can provide the first data for a direct validation and calibration of finite element helmet deformation models, while also providing a new tool-set to improve the efficacy of helmet design.